A laser (non) cutter, or how (not) to make scrambled eggs - Korae, Eva; Vozikis, Athanasios; Satsia, Marisa (My University, 2023)
Once upon a time, two interdisciplinary artists and a designer set out to compose a CO2 Laser Cutting Guide. While undergoing a meticulous procedure to test a wide range of materials in a quest to produce photogenic images of satisfying laser accuracy, they found themselves caught up in a constant effort to reduce human control and produce unpredictable results; on a machine which operates on strict designs and a mere three axes. Questions like “Can we safely cut and engrave polystyrene”, soon evolved into attempts to produce unpredictable polystyrene engravings, while improvising polystyrene dance routines on the laser bed. Could we add a camera to the laser axes to record this unpredictable dance? Soon enough, the booklet to share as a strict glossary of laser possibilities, became a playground of perspectives; a laser cutting guide evolved into an artistic process. This presentation deals with methods where artists use (or misuse) maker tools as a way to exercise artistic expression in new technological environments. Different stages of the process reveal new territories for human-machine collaborations and at the same time unfold further discourse towards the role of computing machines, the role of art / design practitioners and how both potentially address various levels of boundaries, otherness or ways of interpreting progress.